THE EFFECTIVENESS OF PUBLIC VS PRIVATE SCHOOLS IN INDONESIA - Hendajany, Nenny (Journal of Indonesian Applied Economics, 2016)
This paper examines the effectiveness of public versus private schools using the national exit exam of Junior Secondary Schools in Indonesia. Using Indonesian Family Live Survey (IFLS) (1997), IFLS (2000) and IFLS (2007), this study find evidence that graduates of the public school have higher scores on the national exit exam than those of the private school controlling a wide variety of students' characteristics and family background.Â  This finding is robust to several estimates, including Ordinary Least Square (OLS), Fixed Effects (FE), and Instrumental Variable (IV). Using the score of the national exit exam (Ebtanas) as a standard score, public school students are higher 0.30, 0.247 and 0.572 of standard deviations for OLS, FE and IV estimates respectively.Â